Theoretical principles of spatial analysis of the history of administrative-territorial division - Havriushyn, Oleksandr (Human Geography Journal, 2022)
The article considers the theoretical aspects of spatial and spatio-temporal analysis of changes in the administrative-territorial division, its history. It is shown that despite the presence of a significant number of publications on the history of administrative-territorial division, the complex issue of its detailed spatial analysis has not been resolved. The main focus of the author of the article is on diachronic analysis. Levels of analysis are highlighted depending on which object from the history of territorial division is analyzed (one-dimensional linear objects – administrative boundaries, dynamic polygonal objects – administrative units, objects denoting changes, or arbitrary territories and territories with an identical history of administrative affiliation, within which the history of specific objects in the history of administrative-territorial division is summarized with the calculation of the corresponding aggregative indicator). The difference between the study of change as part of the history of specific objects of territorial organization and the study of change as individual spatial objects is described. The principles of allocation of areas of spatial changes, their varieties are described. For each level of analysis, the types of objects that can be units of mapping on analytical or synthetic maps from the history of administrative-territorial division are proposed and described in detail. Typical operations on space-time data on the history of territorial division are considered. Examples of specific indicators on the history of administrative-territorial division that can be calculated for the described objects are given. Differences in the calculation of similar in meaning indicators for objects of different types are described. Particular attention is paid to indicators-aggregates of the history of administrative-territorial division within individual territories. Classifications of such indicators are given. In particular, local aggregates, focal aggregates and aggregates of dynamic objects are distinguished. Examples of the analysis of the administrative reform of 2020 at the district level within the Dnipropetrovsk region are given. The features of comparative analysis of individual states or periods for different objects of change are briefly described.